Chylothorax in the neonate-A stepwise approach algorithm - Rocha, G (2021)
Background: Chylothorax in neonates results from leakage of lymph from thoracic lymphatic ducts and is mainly congenital or posttraumatic. The clinical course of the effusion is heterogeneous, and consensus on treatment, timing, and modalities of measures has not yet been established. This review aims to present, along with levels of evidence and recommendation grades, all current therapeutic possibilities for the treatment of chylothorax in neonates. Methods: An extensive search of publications between 1970 and 2020 was performed in the PubMed, Cochrane Database of Systematic Reviews, and UpToDate databases. A stepwise approach algorithm was proposed for both congenital and traumatic conditions to guide the clinician in a rational and systematic way for approaching the treatment of neonates with chylothorax. Discussion and conclusion: The treatment strategy for neonatal chylothorax generally involves supportive care and includes drainage and procedures to reduce chyle flow. A stepwise approach starting with the least invasive method is advocated. Progression in the invasiveness of treatment options is determined by the response to previous treatments. A practical stepwise approach algorithm is proposed for both, congenital and traumatic chylothoraces.